Method for curing waste soil by using geopolymer prepared from waste glass

Sodium silicate powder is prepared by thermal chemical treatment of waste glass and mixed with industrial waste to form a semipolymer, which solves the problems of low conversion efficiency of waste glass and inconvenient use of cured materials, and realizes efficient utilization of waste glass and safe curing of waste soil.

CN119528468APending Publication Date: 2025-02-28NINGBO UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411807412.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the efficiency of converting waste glass into sodium silicate is not high, and the cured materials prepared are inconvenient to use, making it difficult to widely use in actual engineering.

Method used

The waste glass is heat-chemically treated by alkali, sodium silicate powder is prepared, and mixed with industrial waste materials rich in active silica and alumina to form waste glass-derived polymers for mixing and curing treatment with waste soil.

Benefits of technology

It improves the conversion efficiency of waste glass, solves the problem of disposal of waste glass and waste soil, broadens the resource utilization methods of waste glass, improves the utilization rate of waste glass, and prepares solidified soil with good mechanical properties, durability and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179631620000071
    Figure BDA0005179631620000071
  • Figure BDA0005179631620000081
    Figure BDA0005179631620000081
  • Figure BDA0005179631620000082
    Figure BDA0005179631620000082
Patent Text Reader

Abstract

The invention discloses a method for curing waste soil by using a geopolymer prepared from waste glass, which comprises the following steps: carrying out thermochemical treatment on the waste glass by using alkali to prepare sodium silicate powder; uniformly mixing the prepared sodium silicate powder with industrial wastes rich in active silicon dioxide and aluminum oxide in proportion to obtain a waste glass derived geopolymer; the waste soil and the waste glass derived geopolymer are uniformly mixed in proportion, the mixture is put into a mold and compacted, and curing is performed after demolding to obtain the waste glass derived geopolymer solidified soil. According to the method, the sodium silicate powder prepared from the waste glass is mixed with the industrial waste to generate the waste glass derived geopolymer, the waste soil is solidified, and the conversion efficiency of the waste glass is improved, so that on one hand, the treatment problem of the waste glass and the waste soil is solved, the resource utilization way of the waste glass is widened, and the utilization rate of the waste glass is improved;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil solidification, and in particular relates to a method for preparing geopolymer from waste glass for waste soil solidification treatment. Background Art

[0002] Adding geopolymers to waste soil to improve its properties can not only treat waste soil on a large scale, but also alleviate the shortage of engineering fillers. Currently, the commonly used geopolymers for waste soil are mainly inorganic solidifying materials, such as cement and lime, as well as emerging alkali-activated materials. The development of more energy-saving and environmentally friendly geopolymers is of great significance to the safe disposal of waste soil.

[0003] Since glass has good physical and chemical properties and potential volcanic ash activity, the utilization of waste glass as building materials has become a trend. For example, in the existing document 1, application number 201510540101.2, the invention name is a patent application for a method for preparing fly ash-waste glass powder inorganic polymer sludge solidified material, the waste glass is crushed and mixed with other gelling materials, and then an alkaline solution is added to react to generate a fly ash-waste glass powder inorganic polymer solidified material, and the formed inorganic polymer solidified material is in a slurry state, which is not very convenient to operate, store and use.

[0004] In order to further improve the utilization performance of waste glass, the use of waste glass to make sodium silicate alkali activator has been gradually developed. However, the efficiency of converting waste glass into sodium silicate is not ideal, so the use of waste glass sodium silicate powder activator for soil solidification in actual projects is almost unseen. Summary of the invention

[0005] Aiming at the shortcomings of the prior art such as low efficiency of converting waste glass into sodium silicate and inconvenience in using the prepared solidified material, the present invention provides a method for preparing geopolymer using waste glass for waste soil solidification treatment.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing geopolymer from waste glass for waste soil solidification treatment comprises the following steps:

[0008] Step S1, using alkali to perform thermochemical treatment on waste glass to prepare sodium silicate powder;

[0009] Step S2, mixing the sodium silicate powder prepared in step S1 with industrial waste rich in active silica and alumina in proportion to obtain waste glass-derived geopolymer;

[0010] Step S3, mixing the waste soil and the waste glass-derived geopolymer obtained in step S2 in proportion, placing the mixture into a mold and compacting it, and performing curing after demoulding.

[0011] In step S1 of the present invention, waste glass reacts with sodium hydroxide:

[0012] 2NaOH+SiO2-——Na2SiO3+H2O

[0013] The efficiency of converting waste glass into sodium silicate can be improved by changing whether water is added, the mass ratio of waste glass to sodium hydroxide, the heating temperature and the heating time.

[0014] In the existing document 1, waste glass is used as a precursor material (providing active silica and alumina) to undergo geopolymerization, and the reaction principle is:

[0015] NaOH+(CaO+SiO2+Al2O3)(waste glass+fly ash)——N(C)-ASH(gel material)

[0016] In the present invention, waste glass is used to react with sodium hydroxide to prepare sodium silicate, and then used as an alkali activator to react with industrial waste. The reaction principle is:

[0017] (CaO+SiO2+Al2O3)(slag powder)+Na2SiO3(waste glass sodium silicate)+H2O——C(N)-ASH(gelatinous material)

[0018] Preferably, in step S1, the waste glass is ground and passed through a 200-800 mesh sieve to obtain waste glass powder; and the alkali in step S1 is granular sodium hydroxide.

[0019] Preferably, in step S1, the mass ratio of waste glass powder to sodium hydroxide is 1-4:1.

[0020] Preferably, the temperature of the thermochemical treatment in step S1 is set to 140-340° C.; the heating time is 1-2 hours; after the synthesized sodium silicate is cooled, it is ground in a mortar and passed through a 50-100 mesh sieve.

[0021] Preferably, the industrial waste in step S2 is one or a mixture of slag powder, fly ash and metakaolin.

[0022] Furthermore, the specific surface area of ​​the industrial waste is ≥400 (m 2 / kg), flow ratio ≥ 95%, 28-day activity index ≥ 95%.

[0023] Preferably, the waste glass-derived geopolymer is obtained by uniformly mixing sodium silicate powder and industrial waste in proportion, and then drying and storing the mixture; in step S2, the mass ratio of sodium silicate powder to industrial waste (precursor material) is 0.16-0.24:1.

[0024] Preferably, the amount of the waste glass-derived geopolymer is 6%-15% of the mass of the waste soil. The present invention can adjust the amount of the geopolymer according to actual needs to form solidified soils of different strengths.

[0025] Preferably, in step S3, the curing temperature is 20±2° C., and the relative humidity is ≥95%; the cured waste glass-derived geopolymer-solidified soil can be used as a roadbed filling, base and subbase construction material.

[0026] A waste glass derived geopolymer is prepared by the above method.

[0027] The beneficial effects of the present invention are:

[0028] In the present invention, waste glass is used to prepare sodium silicate powder, which is mixed with industrial waste to generate waste glass-derived geopolymer, and waste soil is solidified. By improving the conversion efficiency of waste glass, on the one hand, the disposal problem of waste glass and waste soil is solved, the resource utilization path of waste glass is broadened, and the utilization rate of waste glass is improved.

[0029] The sodium silicate prepared by the present invention is in powder form, and is then mixed with a precursor material in a certain proportion according to actual needs to form a single-component alkali-activated material, namely, a waste glass-derived geopolymer, which is also in powder form. The waste glass-derived geopolymer can solidify various types of soil, and the solidified soil is not prone to shrinkage and cracking, and has good mechanical properties, durability and corrosion resistance. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. The replacement of simple parameters in the implementation mode cannot be repeated one by one in the examples, but the present invention is not limited thereto. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be regarded as equivalent replacement methods and should be included in the scope of the present invention.

[0031] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0032] The waste glass powder described in the present invention is waste glass collected in daily life and processed in a grinding plant. The following embodiments all use glass powder obtained by passing through a 600-mesh sieve.

[0033] The soil used in the embodiment was taken from an abandoned undisturbed soil sample in a certain area of ​​Ningbo. The moisture content, liquid limit, plastic limit, specific gravity and other information of the soil sample were tested, as shown in Table 1 below:

[0034] Table 1 Basic information of soil samples

[0035] Moisture content Liquid limit Plastic Limit Liquid Limit Index Plasticity Index proportion 33% 37.8% 21.3% 16.5 0.71 2.66

[0036] In the following examples of the present invention, cement and geopolymers uniformly mixed with commercial sodium silicate and industrial waste are used as control groups; the cement used is 42.5 cement, the commercial sodium silicate used is anhydrous sodium silicate, and the industrial waste used is S95 slag powder. The amount of geopolymer in the present invention is the mass ratio of geopolymer to dry soil, and the amount of alkali activator is the mass ratio of alkali activator sodium silicate powder to slag powder.

[0037] When the waste glass powder used in the following examples is mixed with granular / flaky sodium hydroxide at a ratio of 1:1, the mass of the waste glass powder and the granular / flaky sodium hydroxide is 500g; when the waste glass powder used in the following examples is mixed with granular sodium hydroxide at a ratio of 2:1, the mass of the waste glass powder is 1000g, and the mass of the granular sodium hydroxide is 500g. When the waste glass powder used in the following examples is mixed with granular sodium hydroxide at a ratio of 4:1, the mass of the waste glass powder is 2000g, and the mass of the granular sodium hydroxide is 500g. For the convenience of description and comparison, the geopolymer prepared from waste glass and industrial waste in the following examples of the present invention is called waste glass derived geopolymer, and waste glass derived geopolymer and waste soil are used to prepare waste glass derived geopolymer solidified soil, and the geopolymer obtained by reacting commercial sodium silicate with slag powder is ordinary geopolymer, and ordinary geopolymer and waste soil are used to prepare ordinary geopolymer solidified soil.

[0038] Example 1

[0039] 500g of waste glass powder and 500g of granular sodium hydroxide were mixed in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder, i.e., 200g of water, was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 140°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-140-2w and chemical composition analysis was performed.

[0040] Example 2

[0041] Waste glass powder and granular sodium hydroxide were mixed in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 240°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-240-2w and chemical composition analysis was performed.

[0042] Example 3

[0043] Waste glass powder and granular sodium hydroxide were mixed evenly in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 340°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-340-2w and chemical composition analysis was performed.

[0044] Example 4

[0045] Waste glass powder and granular sodium hydroxide were mixed in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 440°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-440-2w and chemical composition analysis was performed.

[0046] It can be seen from Table 2 that as the heating temperature increases, the Na2SiO3 content in the prepared sodium silicate powder decreases. This is because the melting point of NaOH is about 318°C, and higher process temperatures lead to more complex sodium silicate forms and increase the presence of sodium-rich silicates, such as Na4SiO4 and Na6Si2O7.

[0047] Example 5

[0048] 1000g of waste glass powder and 500g of granular sodium hydroxide were mixed in a ratio of 2:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, that is, 300g of water was added, stirred until thick, and then placed in a high-temperature oven; heated to 340°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was marked as 2-340-2w and chemical composition analysis was performed.

[0049] In Example 5, compared with Example 3, the amount of waste glass powder added is increased. As can be seen from Table 2, the Na2SiO3 content in the prepared sodium silicate powder is reduced.

[0050] Example 6

[0051] Waste glass powder and granular sodium hydroxide were mixed evenly in a ratio of 4:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 340°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 4-340-2w and chemical composition analysis was performed.

[0052] Compared with Examples 3 and 5, Example 6 further increases the amount of waste glass powder added. It can be seen from Table 2 that as the amount of waste glass powder added increases, the Na2SiO3 content in the prepared sodium silicate powder decreases.

[0053] Example 7

[0054] Waste glass powder and flake sodium hydroxide were mixed evenly in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 340°C for 2 hours; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-340-2f and chemical composition analysis was performed.

[0055] Compared with Example 3, Example 7 only changes the form of sodium hydroxide. From Table 2, it can be seen that the sodium silicate powder prepared in Example 3 has the highest Na2SiO3 content, and the granular sodium hydroxide has a large contact area and is more likely to react with the waste glass powder.

[0056] Example 8

[0057] Waste glass powder and granular sodium hydroxide were mixed evenly in a ratio of 1:1 and poured into a crucible; 20% of the weight of the mixed powder was added to the crucible, stirred until thick, and placed in a high-temperature oven; heated to 340°C for 1 hour; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-340-1w and chemical composition analysis was performed.

[0058] Compared with Example 3, the heating time in this example was changed from 2 h to 1 h, and the Na2SiO3 content in the prepared sodium silicate powder increased. This may be due to the instability of the reaction system caused by long-term heating at high temperature, thereby reducing the yield of sodium silicate.

[0059] Example 9

[0060] Waste glass powder and granular sodium hydroxide were mixed in a ratio of 1:1 and poured into a crucible; stirred evenly and placed in a high-temperature oven; heated to 340°C for 1 hour; the mixture was taken out, cooled and ground, passed through a 100-mesh sieve, and dried for storage. The prepared powder was labeled 1-340-2 and subjected to chemical component analysis.

[0061] Compared with Example 8, this example does not add water, and the Na2SiO3 content in the prepared sodium silicate powder is very low, which explains why adding water will cause part of the NaOH to dissolve, and after heating causes the water to evaporate, a micrometer or nanometer-scale NaOH thin layer is precipitated around the glass powder particles, which increases the contact between NaOH and the glass powder particles and is beneficial to the reaction.

[0062] Table 2 Chemical composition of sodium silicate powder prepared from waste glass under different conditions

[0063] Chemical composition <![CDATA[Na2SiO3]]> <![CDATA[Na4SiO4]]> <![CDATA[Na6Si2O7]]> <![CDATA[Na2CO3]]> <![CDATA[CaAl2O4]]> <![CDATA[Na2CaSiO4]]> Amorphous 1-140-2w 67% 0% 0% 0% 3% 0% 30% 1-240-2w 61% 0% 0% 0% 2% 2% 35% 1-340-2w 54% 0% 0% 6% 0% 0% 40% 1-440-2w 17% 3% 11% 2% 0% 2% 65% 2-340-2w 36% 0% 0% 3% 1% 0% 60% 4-340-2w 15% 1% 0% 2% 1% 0% 80% 1-340-2f 18% 2% 0% 4% 1% 0% 75% 1-340-1w 63% 1% 0% 0% 1% 0% 35% 1-340-2 24% 3% 4% 9% 1% 0% 60%

[0064] Waste glass sodium silicate powder was prepared by thermochemical method using waste glass and sodium hydroxide. The purpose was to obtain as much sodium silicate as possible by changing some experimental conditions.

[0065] The data in Table 2 show that when the mass ratio of waste glass to granular sodium hydroxide is controlled at 1:1, the test temperature is controlled between 140-340℃, lasts for 1-2h, and water is added and mixed before heating, the efficiency of preparing sodium silicate from waste glass is relatively appropriate, which can maximize the utilization rate of waste glass. In particular, when the mass ratio of waste glass to granular sodium hydroxide is 1:1, water is added and stirred, the heating temperature is 140℃ for 2 hours (1-140-2w), the heating temperature is 240℃ for 2 hours (1-240-2w), and the heating temperature is 340℃ for 1 hour (1-340-1w), the synthesis efficiency of sodium silicate reaches more than 60%.

[0066] From the perspective of the efficiency of synthesizing sodium silicate and sufficient drying of the powder, the waste glass sodium silicate powder prepared by 1-340-1w in Example 8 was used in the following examples.

[0067] Example 10

[0068] The mass ratio of waste glass-derived geopolymer to waste soil in the waste glass-derived geopolymer-solidified soil of step S3 is 0.06:1, wherein the mass of the dry waste soil is 300 g, the moisture content is about 33%, and the mass of the waste glass-derived geopolymer is 18 g; under this ratio, this embodiment studies the properties of the obtained solidified soil by changing the mass ratio of sodium silicate powder prepared from waste glass to slag powder in the waste glass-derived geopolymer in step S2.

[0069] Among them, the mass ratios of sodium silicate powder prepared from waste glass in the waste glass-derived geopolymer to slag powder are 0.12:1 (the masses of sodium silicate powder and slag powder are 2.16g and 18g respectively), 0.16:1 (the masses of sodium silicate powder and slag powder are 2.88g and 18g respectively), 0.2:1 (the masses of sodium silicate powder and slag powder are 3.6g and 18g respectively), and 0.24:1 (the masses of sodium silicate powder and slag powder are 4.32g and 18g respectively).

[0070] The quality of the raw materials used in the preparation of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil in the following examples is consistent with that of the waste glass-derived geopolymer-stabilized soil in this example.

[0071] In this embodiment, waste glass-derived geopolymer is replaced by ordinary geopolymer, and ordinary geopolymer-solidified soil is prepared with the same mass mixing ratio, which is compared with the waste glass-derived geopolymer-solidified soil prepared from waste glass-derived geopolymer.

[0072] Ordinary geopolymer-stabilized soil includes the following components: ordinary geopolymer: waste soil = 0.06:1; wherein, the commercially available sodium silicate in the ordinary geopolymer: slag powder = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0073] Ordinary cement-stabilized soil includes the following components: cement: waste soil = 0.06:1.

[0074] Under the same conditions, the geopolymer and soil are mixed evenly, and the samples are made with a round acrylic tube sampler (D*H=50mm*100mm). They are cured for 28 days under standard curing conditions of temperature 20±2℃ and relative humidity 95% and above, and the samples are tested for unconfined compressive strength. The compressive strength performance of waste glass-derived geopolymer-stabilized soil is compared with that of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil.

[0075] Table 3 Comparison of compressive strength of different solidified soils in Example 10

[0076]

[0077]

[0078] Table 3 shows that with the increase of the alkali activator dosage, the strength of the stabilized soil increases first and then decreases. When the alkali activator dosage is between 16% and 24%, the strength of the geopolymer stabilized soil is basically higher than that of the cement stabilized soil, while the strength of the waste glass derived geopolymer stabilized soil is close to or even slightly higher than that of the ordinary geopolymer stabilized soil. This shows that the waste glass derived geopolymer stabilized soil at this geopolymer dosage has a strength that is not weaker than that of the ordinary geopolymer stabilized soil and higher than that of the cement stabilized soil.

[0079] Embodiment 11

[0080] The difference between this embodiment and embodiment 10 is that:

[0081] The mass ratio of each component in the waste glass derived geopolymer solidified soil is: waste glass derived geopolymer: waste soil = 0.09:1; wherein, the waste glass sodium silicate powder in the waste glass derived geopolymer: slag powder

[0082] =0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0083] Ordinary geopolymer-stabilized soil includes the following components: ordinary geopolymer: waste soil = 0.09:1; wherein, the commercially available sodium silicate in the ordinary geopolymer: slag powder = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0084] Ordinary cement-stabilized soil includes the following components: cement: waste soil = 0.09:1.

[0085] Under the same conditions, the geopolymer and soil are mixed evenly, and the samples are made with a round acrylic tube sampler (D*H=50mm*100mm). They are cured for 28 days under standard curing conditions of temperature 20±2℃ and relative humidity 95% and above, and the samples are tested for unconfined compressive strength. The compressive strength performance of waste glass-derived geopolymer-stabilized soil is compared with that of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil.

[0086] Table 4 Comparison of compressive strength of different stabilized soils in Example 11

[0087]

[0088]

[0089] Table 4 shows that with the increase of the alkali activator dosage, the strength of the stabilized soil increases first and then decreases. When the alkali activator dosage is between 12% and 24%, the strength of the geopolymer stabilized soil is basically higher than that of the cement stabilized soil, while the strength of the waste glass derived geopolymer stabilized soil is close to or even slightly higher than that of the ordinary geopolymer stabilized soil. This shows that the waste glass derived geopolymer stabilized soil at this geopolymer dosage has a strength that is not weaker than that of the ordinary geopolymer stabilized soil and higher than that of the cement stabilized soil.

[0090] Example 12

[0091] The difference between this embodiment and embodiment 10 is that:

[0092] Waste glass derived geopolymer stabilized soil includes the following components: Waste glass derived geopolymer: Waste soil

[0093] =0.12:1; wherein, waste glass sodium silicate powder in geopolymer: slag powder = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0094] Ordinary geopolymer-stabilized soil includes the following components: ordinary geopolymer: waste soil = 0.12:1; wherein, commercially available sodium silicate in the geopolymer: slag powder = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0095] Ordinary cement-stabilized soil includes the following components: cement: waste soil = 0.12:1.

[0096] Under the same conditions, the geopolymer and soil are mixed evenly, and the samples are made with a round acrylic tube sampler (D*H=50mm*100mm). They are cured for 28 days under standard curing conditions of temperature 20±2℃ and relative humidity 95% and above, and the samples are tested for unconfined compressive strength. The compressive strength performance of waste glass-derived geopolymer-stabilized soil is compared with that of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil.

[0097] Table 5 Comparison of compressive strength of different solidified soils in Example 12

[0098]

[0099]

[0100] Table 5 shows that with the increase of the alkali activator dosage, the strength of the solidified soil has been increasing. When the alkali activator dosage is between 16% and 24%, the strength of the geopolymer solidified soil is basically higher than that of the cement solidified soil, while the strength of the waste glass derived geopolymer solidified soil is close to or even slightly higher than that of the ordinary geopolymer solidified soil. This shows that the waste glass geopolymer solidified soil at this geopolymer dosage has a strength that is not weaker than that of the ordinary geopolymer solidified soil and higher than that of the cement solidified soil.

[0101] Embodiment 13

[0102] The waste glass sodium silicate powder prepared by 2-340-1w in Example 8 was used to carry out the following example.

[0103] Waste glass derived geopolymer stabilized soil includes the following components: Waste glass derived geopolymer: Waste soil

[0104] =0.15:1; wherein, the waste glass sodium silicate powder: slag powder in the waste glass derived geopolymer = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0105] Ordinary geopolymer-stabilized soil includes the following components: ordinary geopolymer: waste soil = 0.15:1; wherein, the commercially available sodium silicate in the ordinary geopolymer: slag powder = 0.12:1, 0.16:1, 0.2:1, 0.24:1.

[0106] Ordinary cement-stabilized soil includes the following components: cement: waste soil = 0.15:1.

[0107] Under the same conditions, the geopolymer and soil are mixed evenly, and the samples are made with a round acrylic tube sampler (D*H=50mm*100mm). They are cured for 28 days under standard curing conditions of temperature 20±2℃ and relative humidity 95% and above, and the samples are tested for unconfined compressive strength. The compressive strength performance of waste glass-derived geopolymer-stabilized soil is compared with that of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil.

[0108] Table 6 Comparison of compressive strength of different solidified soils in Example 13

[0109]

[0110]

[0111] Table 6 shows that with the increase of the alkali activator dosage, the strength of the solidified soil increases first and then decreases. When the alkali activator dosage is between 16% and 24%, the strength of the geopolymer solidified soil is basically higher than that of the cement solidified soil, while the strength of the waste glass derived geopolymer solidified soil is close to or even slightly higher than that of the ordinary geopolymer solidified soil. This shows that the waste glass geopolymer solidified soil at this geopolymer dosage has a strength that is not weaker than that of the ordinary geopolymer solidified soil and higher than that of the cement solidified soil.

[0112] Comparing the data in Tables 3, 4, 5 and 6, it can be clearly found that with the increase in the amount of geopolymer, the strength of the solidified soil shows an increasing trend, and the strength gap between geopolymer solidified soil and cement solidified soil is increasing. Waste glass derived geopolymer solidified soil has a strength that is no less than that of ordinary geopolymer solidified soil. Waste glass sodium silicate powder and slag powder are mixed in different proportions to form geopolymers of different strengths. The corresponding grade of waste glass derived geopolymer solidified soil is selected according to the actual engineering needs.

[0113] Take the waste glass sodium silicate powder prepared by 1-340-1w in Example 8 and carry out Example 14.

[0114] Embodiment 14

[0115] Waste glass derived geopolymer stabilized soil includes the following components: Waste glass derived geopolymer: Waste soil

[0116] =0.09:1; wherein, the waste glass sodium silicate powder in the geopolymer: slag powder = 0.2:1.

[0117] Ordinary geopolymer-stabilized soil comprises the following components: ordinary geopolymer: waste soil = 0.09:1; wherein, in the geopolymer, commercially available sodium silicate: slag powder = 0.2:1.

[0118] Ordinary cement-stabilized soil includes the following components: cement: waste soil = 0.09:1.

[0119] Under the same conditions, the geopolymer and soil are mixed evenly, and the samples are made with a round acrylic tube sampler (D*H=50mm*100mm). They are cured for 28 days under standard curing conditions of temperature 20±2℃ and relative humidity 95% and above, and the samples are subjected to 12 dry-wet cycle tests in sodium sulfate solutions with concentrations of 0%, 5%, and 10%. The performance of waste glass-derived geopolymer-stabilized soil is compared with that of ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil, including unconfined compressive strength and mass loss rate.

[0120] The waste glass derived geopolymer-solidified soil was recorded as 14-9G20SS, the ordinary geopolymer-solidified soil was recorded as 14-9G20CS, and the ordinary cement-solidified soil was recorded as 14-9OPC.

[0121] Table 7 Comparison of performance of different solidified soils in Example 14

[0122]

[0123]

[0124] The mass loss rate in Table 7 is obtained by dividing the difference between the sample mass and the initial mass by the initial mass after 12 dry-wet cycles. The smaller the mass loss value, the better the performance of the cured soil sample and the better the sulfate erosion resistance.

[0125] According to the contents in Tables 3-7, the mechanical properties, durability and sulfate corrosion resistance of waste glass-derived geopolymer-stabilized soil, ordinary geopolymer-stabilized soil and ordinary cement-stabilized soil are compared. The data show that the waste glass-derived geopolymer-stabilized soil of the present invention has better performance than ordinary cement-stabilized soil and is not inferior to ordinary geopolymer-stabilized soil, and can bring more environmental and economic effects.

[0126] The above specific implementation methods are preferred embodiments for facilitating understanding of the present invention, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing geopolymer from waste glass for waste soil solidification treatment, characterized in that: The steps include: Step S1, using alkali to perform thermochemical treatment on waste glass to prepare sodium silicate powder; Step S2, mixing the sodium silicate powder prepared in step S1 with industrial waste rich in active silica and alumina in proportion to obtain waste glass-derived geopolymer; Step S3, mixing the waste soil and the waste glass derived geopolymer obtained in step S2 in proportion, placing the mixture into a mold and compacting it, and performing curing after demoulding to obtain waste glass derived geopolymer solidified soil.

2. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 1, characterized in that: In step S1, the waste glass is ground and passed through a 200-800 mesh sieve to obtain waste glass powder; and the alkali in step S1 is granular sodium hydroxide.

3. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 2, characterized in that: In the step S1, the mass ratio of waste glass powder to granular sodium hydroxide is 1-4:

1.

4. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 3, characterized in that: In step S1, the heating temperature of the thermochemical treatment is set to 140-340° C., and the heating time is 1-2 hours; the synthesized sodium silicate is cooled, ground, and then passed through a 50-100 mesh sieve.

5. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 1, characterized in that: The industrial waste in step S2 is one or a mixture of slag powder, fly ash and metakaolin.

6. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 5, characterized in that: The specific surface area of ​​the industrial waste is ≥400 (m 2 / kg)、current ratio≧ 95%, 28-day activity index ≧95%.

7. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 6, characterized in that: The mass ratio of sodium silicate powder to industrial waste in step S2 is 0.16-0.24:

1.

8. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 1, characterized in that: In step S3, the curing temperature is 20±2° C., and the relative humidity is ≥95%.

9. The method for preparing geopolymer from waste glass for waste soil solidification treatment according to claim 1, characterized in that: In step S3, the amount of the waste glass-derived geopolymer is 6%-15% of the mass of the waste soil.

10. A waste glass derived geopolymer, characterized in that: Prepared according to the method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of fly ash-waste glass powder inorganic polymer silt-solidifying material

    CN105152585A